2006
DOI: 10.3164/jcbn.39.40
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid-Induced Lipid Peroxidation and Urinary Excretion of Mercapturic Acid in Rats

Abstract: Summary We hypothesized a suppressive mechanism for dietary docosahexaenoic acid (DHA)-induced tissue lipid peroxidation in which the degradation products, especially aldehydic compounds, are conjugated with glutathione (GSH) through catalysis by glutathione S-transferases (GSTs), and then excreted into urine as mercapturic acids. Sprague-Dawley rats were fed a diet containing DHA (8.4 % of total energy) for 31 days. Lipid peroxides in the liver and kidney, liver GST and urinary excretion of mercapturic acid w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In addition, the excretion on day 28 tended to be higher with DHA intake. This result on day 28 was similar to our previous report [ 27 ]. We have reported the gene expression of dietary DHA-induced multidrug resistance-associated protein 3 in the liver [ 40 ], which could mediate the transport of reactive aldehydes conjugated with GSH into blood stream from the liver.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the excretion on day 28 tended to be higher with DHA intake. This result on day 28 was similar to our previous report [ 27 ]. We have reported the gene expression of dietary DHA-induced multidrug resistance-associated protein 3 in the liver [ 40 ], which could mediate the transport of reactive aldehydes conjugated with GSH into blood stream from the liver.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, therefore, we focused in particular on detoxification and/or excretion mechanisms for suppressing the accumulation of lipid peroxides and their degradation products induced after DHA intake. Our previous study showed that DHA ingestion elevated the urinary excretion of mercapturic acids on day 28 in Sprague-Dawley rats [ 27 ]. Hence, we measured here the temporal change in the urinary excretion of mercapturic acids in AsA-requiring Osteogenic Disorder Shionogi/Shi-od/od (ODS) rats after DHA intake.…”
Section: Introductionmentioning
confidence: 99%